Work readiness profile : a criterion-referenced tool to assist in the initial assessment of inviduals with disabilities - Rowe, Helga A. H. (Helga Anneliese Hildegard) (Camberwell, Vic. : ACER, 1995)
Overview. Administration. Scoring and interpretation. Technical considerations. Cautions, uses and issues.
Keywords: Employment; Handicapped; Psychological testing; Handicapped -- Employment; Handicapped -- Functional assessment; Handicapped -- Psychological testing